VERIFIKASI UJI CEPAT KOMERSIAL Escherichia coli PADA CONTOH UJI DAGING SAPI BEKU (Verification of Escherichia coli Commercial Rapid Test Kit on Frozen Meat) - Yasmine Qurrota Ayunina; Trioso Purnawarman; Surachmi Setiyaningsih (Jurnal Kedokteran Hewan, 2016)
This study was aimed to assess the performance and suitability of commercial rapid test compared to the conventional test through verification process. This study used frozen meat from laboratory routine samples which divided into five groups, those were: natural group, low bacteria level group, medium bacteria level group, high bacteria level group, and control group, each sample test performed 9 replicates. All samples were tested for E. coli by conventional method (SNI 2897:2008) and commercial rapid test method. E. coli test result from both methods was calculated as precision (relative standard deviation), sensitivity, specificity, false negative, false positive, and kappa. The results showed that the commercial kit test had good precision with relative standard deviations score was 0.103. The sensitivity, specificity, false negative, false positive, and kappa score were 94.44%, 100%, 5.56%, 0%, and 0.872, respectively, indicates an equal performance with conventional method. The t student test showed that commercial rapid test method and conventional method had suitability on natural group, low bacteria levels group and medium bacteria level group.